Comparative analysis of four kinds of jumps in volleyball - Pang, J.; Lam, C. P. (2001)
The modern volleyball match trends to focus on the contest over the net. Both in spiking and blocking, good jump ability is necessary for all players. There are four kinds of jumps in volleyball: standing vertical jump, run-up jump in one-foot, run-up jump in two feet and jump from rear row. Among them, the attack with the jump from rear row becomes more and more important in a modern volleyball match and has been widely used in matches. The subjects were eight high-level volleyball players in Macau. The above four kinds of jumps were studied. The kinematic, dynamic and EMG data were collected synchronously by the Motion Analysis System, Kistler Forceplate and Noraxon Myosoft 2000 16 channel EMG Analysis System respectively. Ten markers were attached to neck, foot, left and right hip, left and right knee, left and right ankle, left and right toe. Electrodes were also attached to four muscles: rectus femoris, semitendinosus, tibialis and gastrocnemius of right leg. The result indicated that: (1) among the four kinds of jumps, the highest height was achieved with run-up jump in two feet; (2) the longest time in the air also appeared in run-up jump in two feet in the four kinds of jump; (3) the highest horizontal velocity was in jump from rear row and (4) the rectus femoris and gastrocnemius were the main muscles during jump, but the function of semitendinosus should not be neglected.